Electric‐Tunable Photoluminescence of 2D ErOCl for High‐Security Encryption of Programmable Information. Issue 16 (29th May 2022) - Chen, Ping; Li, Dongyan; Li, Zexin; Pi, Lejing; Xu, Xiang; Wang, Haoyun; Zhou, Xing; Zhai, Tianyou
Abstract: High‐security encryption has always been important in economic and military fields as well as in daily life. 2D van der Waals (vdW) rare‐earth (RE) materials have advantages in photoluminescence (PL) modulation to achieve high‐security encryption because of their multiple sharp emission peaks, which will facilitate the multimode regulation for high‐security encryption of programmable information. Here, programmable information encryption has been achieved by applying 2D vdW ErOCl via the editable electric‐tunable PL. The correct information encoded in PL outputs can be tactfully decrypted from the PL intensity ratio of 2 H11/2 – 4 I15/2 and 4 S3/2 – 4 I15/2 transitions. This strategy for ASCII codes and images encryption with high‐security is demonstrated. This novel approach, PL modulation of 2D vdW RE material based on programmable electric inputs, will mark a new path to achieve high‐security encryption. Abstract : This work reports the programmable information encryption by 2D van der Waals rare‐earth material ErOCl based on the editable electric‐tunable photoluminescence (PL). The correct information encoded in PL outputs can be tactfully decrypted from the PL intensity ratio of two thermal coupling transitions ( 2 H11/2 – 4 I15/2 and 4 S3/2 – 4 I15/2 ), which has been applied to ASCII codes and images encryption with high‐security.